Scombroid poisoning among prisoners of a prison in Johor, Malaysia - Dapari, Rahmat; Ab Razak, Muhamad Farhan; Ahmad Bahuri, Nor Hana; Subahir, Mohamad Nizam; Ibrahim, Farha; Tok, Peter Seah Keng; Toha, Haidar Rizal; Hassan, Mohd Rohaizat; Hod, Rozita; Mohd Ghazali, Qistina; Ahmad Zamzuri, Mohd ‘Ammar Ihsan; Syed Abdul Rahim, Syed Sharizman (Malaysian Journal of Public Health Medicine, 2024)
Scombroid poisoning is a food poisoning caused by ingesting contaminated fish from the Scombridae family, which presented as an allergic reaction due to over-histamine release. On 15th of April 2019, Kluang District Health Office received notification of a suspected food poisoning outbreak among prisoners in Johor, Malaysia following several of them experiencing allergic reactions after consumption of fish during dinner. Thus, this study aimed to describe the epidemiological characteristics of the outbreak, determine the extent and causative agent and make recommendations on the control and preventive measures. In this study, a case is delineated as a prisoner confined at Kluang Prison A displaying symptoms of scombroid poisoning—urticaria, respiratory distress, headache, eye redness, fever, or diarrhoea—after consuming fried ikan tongkol and mackerel during dinner on April 15, 2019, from 16:30 to 22:00 hours. Data on demographic characteristics, the onset of food poisoning and allergic symptoms, critical control point assessment of raw fish, food intake history and food preparation method were obtained. Of 3156 prisoners 30 (0.95% attack rate) were infected during this outbreak. Five prisoners were referred to the hospital and 3 of them were required admission. Predominant clinical features were urticaria (96.7%), shortness of breath (66.7%), eye redness (56.7%), fever (46.7%) and diarrhoea (36.7%). Moreover, the study revealed that fried mackerel fish has a high histamine level (430.3 mg/kg). The poisoning occurs due to a breach in critical control point during fish preparation. The outbreak was declared free on 16 April 2019. The scombroid poisoning outbreak in Kluang Prison A was conclusively attributed to spoiled mackerel fish. The investigation revealed significant lapses in food cleanliness within the prison, with a notable contribution to cross-contamination by food handlers. The findings underscore the importance of collaborative efforts among the prison administration, prisoners, and health officers to prevent future incidents of food poisoning.